Psychoactive substances, alcohol and tobacco consumption in HIV-infected outpatients. (1st June 2018) - Jacquet, Jean-Marc; Peyriere, Hélène; Makinson, Alain; Peries, Marianne; Nagot, Nicolas; Donnadieu-Rigole, Hélène; Reynes, Jacques
Abstract : Objectives: To assess the alcohol consumption, tobacco addiction and psychoactive substance use (PSU) of people living with HIV (PLHIV). Design: Cross-sectional study in an HIV outpatient unit. Methods: Autoquestionnaire systematically proposed to all patients during their usual clinical care visit during a 6-months period, for alcohol (AUDIT test), tobacco (Short Fagerstrom Test) and PSU (ASSIST V3.0 test). Results: Of 1334 distributed questionnaires, 1018 PLHIV responded: 76.8% were men [528 patients were MSM), and the median age was 49 years (interquartile range: 42–46). A prevalence of excessive alcohol drinking was found in 22% [95% confidence interval (CI) 19.5–24.7%] and 44.6% (CI 41.5–47.7%) were current smokers, with high dependence in 29.1% (CI 24.9–33.7%). The prevalence of PSU was 37.8% (CI 34.8–41%) in the past 3 months: cannabis 27.7%, poppers 16.4%, cocaine 8.9%, psychotropic medications 7.1%, gamma-hydroxybutyrate/gamma-butyrolactone (GHB/GBL) 4.7%, stimulants 3.1%, synthetic cathinones 2.7%, hallucinogens 1.5%. In the past 3 months, PSU was more prevalent in MSM than in non-MSM patients (46 versus 30%, P  < 0.001). MSM consumed significantly more inhaled solvents (poppers) 31.0 versus 1.1%, GHB/GBL 7.8 versus 0.8%, stimulants 5.0 versus 1.1%, synthetic cathinones 4.9 versus 0.3%, and hallucinogens 2.3 versus 0.5%. Conclusion: Given the high prevalence of PSU and other addictions (alcohol and smoking) among PLHIV, and particularly among MSM, a systematic screening of PSU and other addictions should be part of routine clinical care.